Infrastructure to Culture: A Qualitative Case Study of Hospital Disaster Preparedness Using Hospital Safety Index as Contextual Assessment - Mahardhika Zulfa Ashidiqi; Ekorini Listiowati; Yuyun Pramayanti; Yuanita Wulandari; Mohammad Agus Samsudin; Corona Rintawan (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Hospitals are expected to remain fully functional during disasters; however, many facilities continue to face structural, operational, and organizational constraints that limit their resilience. The Hospital Safety Index (HSI) provides a standardized metric for assessing a facility’s capacity to withstand and operate during emergencies, yet limited studies in Indonesia have integrated HSI assessments with qualitative insights from frontline staff. This study examines disaster preparedness at PKU Muhammadiyah Gamping Hospital, a Type B teaching hospital in Yogyakarta, to generate a comprehensive understanding of its strengths and vulnerabilities. Methods: This study employed a qualitative case study approach to explore hospital disaster preparedness within its organizational context. Semi-structured interviews were conducted with 12 purposively selected informants from clinical, technical, and managerial units. Qualitative data were analyzed thematically using NVivo.Additionally, Hospital Safety Index (HSI) scores obtained from a retrospective assessment conducted in June 2025, using the 2015 HSI module, were used as contextual reference information. The HSI findings were not integrated analytically but served to complement and contextualize the qualitative insights on organizational preparedness.. , Results: The hospital achieved an overall HSI score of 0.69 (Category A), indicating a high likelihood of remaining functional during disasters. Structural (0.68) and non-structural (0.77) components demonstrated strong performance, supported by reliable utilities, protective installations, and adequate logistics. In contrast, emergency and disaster management scored lower (0.59, Category B), reflecting outdated disaster plans, uneven staff awareness of emergency procedures, limited training frequency, and the absence of a designated disaster preparedness budget. These quantitative findings were further reinforced by qualitative insights, which highlighted gaps in committee activation, surge capacity planning, and routine simulation exercises, although external coordination with fire services, police, and the Muhammadiyah hospital network emerged as a key strength. Conclusion: This study suggests discrepancy the possibility between physical resilience and organizational readiness in the study hospital. While findings are context-specific, they suggest that strengthening leadership commitment, institutionalizing disaster financing, updating preparedness plans, and embedding regular multidisciplinary training may enhance operational resilience in similar healthcare settings.